In the absence of evidence, who chooses? A qualitative study of patients' needs after treatment for colorectal cancer. - Rozmovits, L; Rose, P; Ziebland, S (2004)
OBJECTIVES: To identify the range of patient pathways following surgery for colorectal cancer and explore patients' needs and preferences for follow-up. METHODS: A survey of hospitals within the UK Colorectal Cancer Services Collaborative and qualitative thematic analysis of 39 in-depth narrative interviews with colorectal cancer patients. Participants volunteered or were contacted through hospital consultants, support groups and general practitioners (GPs). Most of the interviews were collected in respondents' homes, throughout the UK. RESULTS: Thirty-five (70%) hospitals supplied details of their follow-up regime. There was a wide variation: only three hospitals specifically stated that patients were given a choice about the type of follow-up. The patients' interviews highlighted their need for a responsive GP and realistic information about recovery, resources and diet. Choice is particularly important because patients differ in their views of the benefits of hospital follow-up. CONCLUSIONS: The absence of evidence about what constitutes ideal clinical follow-up for colorectal cancer is reflected in current hospital practice. In such circumstances, the preferences of individual patients are particularly important. Not all patients want repeated specialist investigations but those without stomas, and therefore no access to a stoma nurse, need another source of advice about recovery and long-term practical help. Follow-up care organised by GPs may be acceptable to many patients. We suggest a list of topics for GPs to discuss with their patients about follow-up. The needs described by patients are not extensive and could often be met by existing resources.